Analysis of muscular endurance, maximum torque, maximum power and total work on the isokinetic dynamometer at 180°/s in individuals 6 months after anterior cruciate ligament (ACL) reconstruction (Research, Society and Development, 2022)
The Anterior Cruciate Ligament (ACL) is an important stabilizer of the knee and aids in joint proprioception and arthrokinematics. The incidence of ACL injury is mainly in surgical procedures, treatment for public treatment. Strength is one of the factors that are not, however, the muscle return, which has a role in the characteristics of the lower limbs, which is always an ACL maneuver. The study was mainly analyzed how muscle fatigue behaves, in after 6 months of reconstruction of the ACL reconstruction objective, the 180° Biodex/Sistema brand after analysis. In addition to muscular endurance, maximum power and total work data were also superior. It was observed after 6 months of reconstruction that the extensor muscle group of the injured limb index showed less fatigue compared to the extensor group of the injured limb. Regarding maximum torque, maximum power and total work, the knee extensor muscle group affected showed a deficit greater than 10% in relation to the healthy limb extensor muscle group. Regarding the knee flexor muscle group, no significant differences were observed between the members in studies of the sessions. Therefore, it is suggested that more studies be carried out that use an analysis at 180°/s in the Isokinetic Dynamometer, for a better use of the data, aiming at a safer sports return.